Hubungan Kadar Timbal dalam Darah terhadap Kejadian Hipertensi pada Operator SPBU di Kota Kendari - Noviarsih Muslimah; Hartati Hartati; Fedelia Raya (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2017)
ABSTRACTHypertension is a common health problem and often asymptomatic until advanced stages of development and often leads to death. One of the factors that play a role in the occurrence of hypertension is a heavy metal, that is lead (Pb) which is used as an additional chemical mixture of gasoline. Gas station’s operator is one of the jobs are high-risk exposure to lead for a long time. This study aims to determine the association of blood lead levels with incidence of hypertension among the gas station’s operators in Kendari. This study used cross sectional design with observational analytic approach. The study was conducted at nine stations in Kendari and Forensic and Molecular Biology Laboratory, Faculty of Mathematics and Science, Haluoleo University, Kendari on 16 - 20 December 2016. Sample consisted of 30 operators of gas station, using proportional stratified sampling technique. The instrument used in this study were questionnaires and testing blood specimens in the laboratory by ashing method. Analysis of the data used in this study was Fisher Exact Test. The result showed respondents with normal blood lead levels are 6 respondents (20.0%) and abnormal blood lead levels are 24 respondents (80.0%). Respondents who have hypertension are 26 respondents (86.7%) and respondents who did not have hypertension are 4 respondents (13.3%). Respondents with normal lead levels who had hypertension totaled 2 respondents (6.7%) and who do not have hypertension totaled 4 respondents (13.3%). Respondents with abnormal lead levels who had hypertension totaled 24 respondents (100.0%) and who do not have hypertension numbered 0 respondents (0.0%). Based on the result of data analysis using the Fisher Exact statistical tests on the correlation of blood lead levels in the incidence of hypertension among the gas station’s operators  in Kendari, p value = 0.001 which means that H0 is rejected. There is correlation between blood lead level with incidence of  hypertension among the gas station’s operators in Kendari .Keywords: Lead in the blood, hypertension, gas station’s operator